GENDER INCLUSION IN BHARATANATYAM: A QUANTITATIVE RESEARCH OF KNOWLEDGE AND ATTITUDES BY DANCE PRACTITIONERS - Himabindu, U; Basa, Murali; Savalapurapu, Bhargavi; Rajbhangshi, Olympica (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The issue of gender inclusiveness has grown more and more important in Indian classical dance styles, specifically in Bharatanatyam, a dance that was historically conditioned by adherence to strict gender conventions, canons of classic aesthetics, and heteronormative discourse. Although the last several decades have seen an increase in the involvement of male, transgender, and non-binary performers, the issues of acceptance, representation, and equality remain still in the institutional and pedagogical environment. The current research investigates the level of knowledge, gender discrimination attitudes among dance practitioners with a particular view to Bharatanatyam. Data were gathered using descriptive cross-sectional survey design and it was collected on 141 respondents with varying demographic backgrounds. Analysis was done using descriptive statistics and Chi-square tests. The results show that there is an equal distribution of the knowledge about gender discrimination across the demographic variables, and the attitudes towards gender discrimination are significantly correlated with gender (p <.05). The paper identifies an urgent gap between awareness and attitudinal acceptance and suggests the continuation of pedagogical, institutional, and cultural interventions to create the conditions of real gender inclusivity in Bharatanatyam.